2008
DOI: 10.1007/s11104-008-9589-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus acquisition characteristics of cotton (Gossypium hirsutum L.), wheat (Triticum aestivum L.) and white lupin (Lupinus albus L.) under P deficient conditions

Abstract: A rhizobox experiment was conducted to examine the P acquisition characteristics of cotton (Gossypium hirsutum L.), wheat (Triticum aestivum L.) and white lupin (Lupinus albus L.) under P-deficient conditions. We aimed to identify whether cotton is physiologically efficient at acquiring P through release of protons, phosphatases or carboxylates. Plants were pre-grown in the upper compartment of rhizoboxes filled with a sand and soil mixture to create a dense root mat against a 53 μm polyester mesh. For each sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 47 publications
8
56
2
Order By: Relevance
“…In the PS treatment, BUE ranged from 16.27 (MT 124) to 5.99 (MT 110) g g -1 , while in the PD treatment, it ranged from 9.67 to 1.59 g g -1 . In another study, significant BUE differences were observed in six cotton genotypes cropped under both low and sufficient P conditions (Wang et al, 2008). In the present study, it was higher in MT 102, MT 105, and MT 112 for the PS and PD treatments (Table 4).…”
Section: Rodmsupporting
confidence: 58%
See 3 more Smart Citations
“…In the PS treatment, BUE ranged from 16.27 (MT 124) to 5.99 (MT 110) g g -1 , while in the PD treatment, it ranged from 9.67 to 1.59 g g -1 . In another study, significant BUE differences were observed in six cotton genotypes cropped under both low and sufficient P conditions (Wang et al, 2008). In the present study, it was higher in MT 102, MT 105, and MT 112 for the PS and PD treatments (Table 4).…”
Section: Rodmsupporting
confidence: 58%
“…With regards to ARE, it was higher in MT 101, MT 92, and MT 124 than in other genotypes, and it exhibited, on the average, 6% of accumulated P in the plant per applied P unit. This result shows the best P recovery from fertilizer by these genotypes (Wang et al, 2008). Cotton response to soil P application in soil in the Cerrado is higher than that of rice cropped under similar conditions in the highlands.…”
Section: Rodmmentioning
confidence: 71%
See 2 more Smart Citations
“…P efficiency studies require two levels of P availability to identify efficient and inefficient cultivars (Fageria & Baligar, 1997;Ahmad, Hans-peter, Johann, Josef, & Walter, 2014). Although previous research has found a strong correlation between cotton P uptake and the proportion of P bonded to iron and aluminum oxides (Dohary, Rochester, & Blair, 2004;Wang, Tang, Guppy, & Sale, 2008) as well as a weak correlation between cotton P uptake and P fertilization in alkaline soils (Bronson et al, 2001), further work is needed to better understand and evaluate the P use efficiency of cotton plants.…”
Section: Introductionmentioning
confidence: 98%